1996
DOI: 10.1111/j.1553-2712.1996.tb03515.x
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Clinically Significant Plain Radiograph Misinterpretation by Faculty in an Emergency Medicine Residency Program

Abstract: Objective:To estimate the rate of clinically significant discrepancies between radiograph interpretations by attending radiologists and emergency medicine (EM) faculty in 2 academic EDs, using a unique scoring system. Methods:A retrospective comparison of radiographic agreement between EM and radiology faculty members was performed. All plain films initially interpreted by EM faculty or by EM residents with immediate reinterpretation by EM faculty were subsequently reviewed by attending radiologists. All discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
2
38
2
Order By: Relevance
“…It is worth mentioning that in the literature one can find reports of discrepancy as high as 13.2% between readings of the same radiologic study by two radiologists (9). Therefore, it is recommended to use a panel of radiologists to improve the quality of the research (5, 12, 18, 19). False radiologic interpretations have been described differently in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that in the literature one can find reports of discrepancy as high as 13.2% between readings of the same radiologic study by two radiologists (9). Therefore, it is recommended to use a panel of radiologists to improve the quality of the research (5, 12, 18, 19). False radiologic interpretations have been described differently in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some practices allow non-radiologists to interpret imaging studies. Multiple studies have reported a broad range of discrepancy rates between radiologists and non-radiologists, however, of the noted discrepancies, many fell into categories our review found to be high-litigation diagnoses such as missed fractures and pulmonary nodules or malignancies [3][4][5][6]. It is our goal to improve prompt identification of these important findings by recommending the adoption of comparable review processes whereby a radiologist "over-reads" imaging studies initially interpreted by non-radiologists.…”
Section: Radiology Interpretation Errorsmentioning
confidence: 91%
“…9 One reason for missing a fracture is that the physician may be concentrating on another injury and does not obtain a radiograph of the site of the fracture. 10 In the patients included in our study, radiographs were obtained; however, because of incorrect request of oblique view instead of lateral, incorrect positioning despite correct request, or superimposition of other fingers, either the fracture was not visible on the radiograph or the displacement was not evident on the radiograph. Among seven patients in whom a fracture was missed, the AP and lateral views were appropriately requested in three patients (the thumb in one case and the other fingers in two cases).…”
Section: Discussionmentioning
confidence: 99%